The effect of risk management a awareness on financial performance of small and medium enterprises in Oman - Al Qubtan, Taha Redha Taqi (Tanjong Malim, 2023)
The effect of risk management a awareness on financial performance of small and medium enterprises in Oman by Al Qubtan, Taha Redha Taqi